2013
DOI: 10.1021/ac3026465
|View full text |Cite
|
Sign up to set email alerts
|

Direct Approach for Qualitative and Quantitative Characterization of Glycoproteins Using Tandem Mass Tags and an LTQ Orbitrap XL Electron Transfer Dissociation Hybrid Mass Spectrometer

Abstract: The application of multiplexed isobaric tandem mass tag (TMT) labeling and an LTQ Orbitrap XL ETD (electron transfer dissociation) hybrid mass spectrometer as a direct approach for qualitative and quantitative characterization of glycoproteins is reported. Bovine fetuin was used as a model glycoprotein in this study. For online liquid chromatography-mass spectrometry (LC-MS) analysis, high-resolution, mass accurate full scan MS spectra were acquired in the Orbitrap mass analyzer followed by data-dependent tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 43 publications
(60 reference statements)
3
70
0
Order By: Relevance
“…For glycopeptides with attached glycans, oxonium ion intensities were observed to be higher than the intensities of the iTRAQ reporter ions, and the diagnostic oxonium ions were the base peak in MS/MS. In previous studies, a similar phenomenon was observed when tandem mass tags (TMT) were used for the analysis of bovine fetuin/glycosidic bonds were preferentially cleaved versus amides in HCD fragmentation (23,24). To extract the MS/MS spectra of glycopeptides from the global proteomic data, we required the oxonium ion intensities to be greater than the highest iTRAQ reporter ion intensity.…”
Section: Resultsmentioning
confidence: 82%
“…For glycopeptides with attached glycans, oxonium ion intensities were observed to be higher than the intensities of the iTRAQ reporter ions, and the diagnostic oxonium ions were the base peak in MS/MS. In previous studies, a similar phenomenon was observed when tandem mass tags (TMT) were used for the analysis of bovine fetuin/glycosidic bonds were preferentially cleaved versus amides in HCD fragmentation (23,24). To extract the MS/MS spectra of glycopeptides from the global proteomic data, we required the oxonium ion intensities to be greater than the highest iTRAQ reporter ion intensity.…”
Section: Resultsmentioning
confidence: 82%
“…Based on the online chromatogram, the target fractions were infused for MS analysis followed by subsequent higher-energy collisional dissociation (HCD) and ETD of the selected precursors. Detailed MS settings and parameters were identical to those previously described (28). Briefly, in-source dissociation at 92 V generated characteristic oxonium ions at m/z 204 which were further fragmented by a dedicated MS 3 event for highly sensitive and selective detection of the eluting glycosylated peptides (29).…”
Section: Liquid Chromatography-mass Spectrometrymentioning
confidence: 99%
“…The reported labeling procedure was developed using commercially available fetuin without any excipients (28). To achieve an optimized labeling procedure for the drug products, different approaches were investigated.…”
Section: Tmt Labeling Efficiency Of the Drug Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38] This general behavior has proven very valuable, as application of two complementary methods can enable thorough characterization of glycopeptide composition and structure. [39][40][41][42][43] Unsurprisingly, a number of other glycopeptide ion dissociation pathways have been observed which do not fall within the domain of strictly complementarity vibrational activation/dissociation and electron transfer/ capture dissociation. [44][45][46][47] This includes numerous examples of vibrational activation/dissociation methods providing information not limited to the carbohydrate group, but extending to the amino acid sequence of the peptide group as well.…”
Section: Introductionmentioning
confidence: 99%